IMPROVING TEACHING AND LEARNING MATHEMATICS COURSES IN COMPUTER SCIENCE AND ENGINEERING STUDIES - Dimitrova, Vesna; Popovska Mitrovikj, Aleksandra; CHorbev, Ivan; Joksimoski, Boban (IATED Academy, 2021)
The importance and the role of mathematics courses in solving real-life problems and applications, including software development, are invaluable. However, some students of Computer Science and Engineering do not fully realize the connection and therefore dislike learning mathematics. They do not appreciate the importance and the role of mathematics and some of them think that only hands-on programming and software tools knowledge is sufficient for a good computer science engineer. As mathematics courses are the core of first-year studies of any Computer Science and Engineering studies, sometimes they are the main reason for students’ failure to meet the requirements of first year academic studies and eventually to graduate. One of the projects that aims to improve the learning and teaching of mathematics courses is ITEM (Innovative Teaching Education in Mathematics). The ITEM project plans to develop and test innovative learning and teaching tools, new methodologies and approaches (learning outcomes and ICT based practices) towards building and enhancing students’ mathematics skills. In this paper, we analyse possibilities to improve the teaching and learning of mathematics courses using mathematical software. The ubiquity of computers and mobile devices together with its potential to bridge classroom learning to real-world has added a new angle to contextualizing mathematics learning. We will present the results of а student survey for the experience of using GeoGebra or other similar applications as a tool for mastering the materials for the Calculus course at our faculty. Also, we will analyse the answers to the student questionnaire for their opinion and suggestions for improving the lectures. As a conclusion, we will give some recommendations for solving the mentioned problems and some suggestions for further improvement of teaching and learning mathematics courses.
Keywords: Teaching, learning, mathematics, computer science studies